Understanding the challenges faced by Orang Asli students in solving mathematics problems - Abd Jalil, Abdul Hakim; Abdullah, Abdul Halim (Institute of Advanced Engineering and Science, 2025)
The educational attainment of Orang Asli students, a minority group in Malaysia, particularly in mathematics, has been a persistent concern. Despite this, research on Orang Asli mathematics education, especially in the southern region of Peninsular Malaysia, remains scarce. This study scrutinized the academic performance of Orang Asli students in whole numbers and operations at level 2 of primary school, focusing on their challenges in solving word problems in mathematics. A total of 22 Orang Asli students from year 4 and 5 in two Orang Asli primary schools participated, undertaking a mathematics test comprising five-word problems. The study identified five prevalent errors among Orang Asli students: i) failure to comprehend the question; ii) misconceptions; iii) inability to grasp specific terms in the question; iv) carelessness; and v) poor reading skills. The findings are thoroughly discussed, and strategies to enhance Orang Asli students’ mathematical problem-solving abilities are proposed.